Afraid of Delivering at the Hospital or Afraid of Delivering at Home: A Qualitative Study of Thai Hmong Families’ Decision-Making About Maternity Services - Kathleen A. Culhane-Pera (2018)
© 2015, Springer Science+Business Media New York. Thailand has high rates of maternity services; both antenatal care (ANC) and hospital delivery are widely used by its citizens. A recent Northern Thailand survey showed that Hmong women used maternity services at lower rates. Our objectives were to identify Hmong families’ socio-cultural reasons for using and not using maternity services, and suggest ways to improve Hmong women’s use of maternity services. In one Hmong village, we classified all 98 pregnancies in the previous 5 years into four categories: no ANC/home birth, ANC/home, no ANC/hospital, ANC/hospital. We conducted life-history case studies of 4 women from each category plus their 12 husbands, and 17 elders. We used grounded theory to guide qualitative analysis. Families not using maternity services considered pregnancy a normal process that only needed traditional home support. In addition, they disliked institutional processes that interfered with cultural birth practices, distrusted discriminatory personnel, and detested invasive, involuntary hospital procedures. Families using services perceived physical needs or potential delivery risks that could benefit from obstetrical assistance not available at home. While they disliked aspects of hospital births, they tolerated these conditions for access to obstetrical care they might need. Families also considered cost, travel distance, and time as structural issues. The families ultimately balanced their fear of delivering at home with their fear of delivering at the hospital. Providing health education about pregnancy risks, and changing healthcare practices to accommodate Hmong people’s desires for culturally-appropriate family-centered care, which are consistent with evidence-based obstetrics, might improve Hmong women’s use of maternity services.